Shared biomarkers between female diastolic heart failure and pre‐eclampsia: a systematic review and meta‐analysis. (30th January 2017) - Alma, Lisa J.; Bokslag, Anouk; Maas, Angela H.E.M.; Franx, Arie; Paulus, Walter J.; de Groot, Christianne J.M.
Abstract: Evidence accumulates for associations between hypertensive pregnancy disorders and increased cardiovascular risk later. The main goal of this study was to explore shared biomarkers representing common pathogenic pathways between heart failure with preserved ejection fraction (HFpEF) and pre‐eclampsia where these biomarkers might be potentially eligible for cardiovascular risk stratification in women after hypertensive pregnancy disorders. We sought for blood markers in women with diastolic dysfunction in a first literature search, and through a second search, we investigated whether these same biochemical markers were present in pre‐eclampsia.This systematic review and meta‐analysis presents two subsequent systematic searches in PubMed and EMBASE. Search I yielded 3014 studies on biomarkers discriminating women with HFpEF from female controls, of which 13 studies on 11 biochemical markers were included. Cases had HFpEF, and controls had no heart failure. The second search was for studies discriminating women with pre‐eclampsia from women with non‐hypertensive pregnancies with at least one of the biomarkers found in Search I. Search II yielded 1869 studies, of which 51 studies on seven biomarkers were included in meta‐analyses and 79 studies on 12 biomarkers in systematic review.Eleven biological markers differentiated women with diastolic dysfunction from controls, of which the following 10 markers differentiated women with pre‐eclampsia from controls as well: C‐reactive protein, HDL, insulin, fatty acid‐binding protein 4, brain natriuretic peptide, N terminal pro brain natriuretic peptide, adrenomedullin, mid‐region pro adrenomedullin, cardiac troponin I, and cancer antigen 125.Our study supports the hypothesis that HFpEF in women shares a common pathogenic background with pre‐eclampsia. The biomarkers representing inflammatory state, disturbances in myocardial function/structure, and unfavourable lipid metabolism may possibly be eligible for future prognostic tools.